Increasing Nitrogen Fertilizer Efficiency on Wetland Rice by Using Humic Acid - . Suhardjadinata; Yaya Sunarya; Tenten Tedjaningsih (UNIVERSITY OF LAMPUNG, 2015)
The objective of the research was to study the interaction between dose of humic acid and nitrogen fertilizer on the growth and yield of rice. The experiment was conducted in May until September 2014 in Sukamanah village Cipedes sub-district Tasikmalaya city. A field experiment was done using as split plot design consisted of two factors. The dosage of humic acid were placed as main plot consisted of four levels i.e. 0 kg ha-1, 3 kg ha-1, 4 kg ha-1, and 5 kg ha-1; and the rate of N fertilizer, as subplot, consisted of 4 levels i.e.0 kg N ha-1, 45 kg N ha-1, 67.5 kg N ha-1, and 90 kg N ha-1. The variables observed were: (a) the levels of soil organic C before and after treatment, (b) the levels of crop N, and (c) the components of growth and yield. Nitrogen fertilizer efficiency was expressed in terms of agronomic efficiency of nitrogen (AEN). The results showed that the growth and yield of rice given humic acid was higher than that without humi cacid. The increasing dose of humic acid i.e. 3 kg ha-1, 4 kg ha-1, and 5 kg ha-1 did not have significant effect. A higher response on growth and grain yield was shown at the dose of humic acid 3 kg ha-1. Nitrogen fertilizer gave significant effect on all growth variables and yield of rice. The higher the level of nitrogen fertilizer up to a certain level (i.e. 67.5 kg N ha-1 or equals to 150 kg Urea ha-1), the higher would be the effect on all growth variables and yield. The increase in weight of grain ha-1 due to the increased level of nitrogen fertilizer compared to those without nitrogen fertilizer (control) were respectively 58.05% at 45 kgha-1 N, 150.54% at 67.5 kg ha-1 N, and 168.13% at 90 kg ha-1 N. Humic acid increased the efficiency of N fertilizer. The most efficient dose of N fertilizer was 67 kg ha-1, equal to 150 kg ha-1 combined with humic acid 3 kg ha-1. [How to Cite: Suhardjadinata, Y Sunarya and T Tedjaningsih. 2015. Increasing Nitrogen Fertilizer Efficiency on Wetland Rice by Using Humic Acid. J Trop Soils 20: 143-148. Doi: 10.5400/jts.2015.20.3.143]